Synthesis of (±)-Glabridin via Formation Isoflavone Using DMS/DMF Adduct - Yadav, Santosh Kumar; Yadav, Shiv Kumar (European Journal of Applied Sciences, 2024)
The objective of this work was to investigate the application of methoxymethylene-N, N-dimethyliminium salts (DMS–DMF adducts) as useful reagents for synthesis of (±)-Glabridin via formation Isoflavone Using DMS/DMF adduct as a key step.